EKSPLORE KARAKTERISTIK TARIK, THERMAL DAN MORPHOLOGY KOMPOSIT EPOXY DIPERKUAT SERAT TIMOHO – MIKRO SERBUK Al2O3 - Suteja; Syarif Hidayatullah (Energy, Materials and Product Design, 2026)
Epoxy composites reinforced with natural fibers can be added with a second filler in the form of powder to enhance their performance. This method affects the thermal resistance properties of the composites. This study investigates the development of epoxy composites reinforced with timoho fibers to which an aluminum oxide (Al₂O₃) powder filler has been added. The composites were fabricated using the hand lay-up method, and the tensile properties, thermal conductivity, and fracture morphology of the epoxy composites were analyzed to determine the effect of varying the volume fraction of Al₂O₃ filler on epoxy composites containing 20% (wt) timoho fibers. The results of the investigation showed that the highest tensile strength of 70.41 MPa was obtained by the SA composite, then decreased to 51.15 MPa in the SC composite. The highest thermal conductivity and linear thermal expansion coefficient values for the composites were each found in the SA sample, at 1179.13 W/m·K and 1045.25 °C, respectively. SEM morphology revealed that the timoho fibers experienced fiber pull-out and cracks in the epoxy matrix. Overall, the SEM images support the tensile strength values.